Skink on the brink - Del Rizzo, Suzanne (Fitzhenry & Whiteside, 2013)
Stewie is a very special skink - he has a beautiful blue tail which gives him a superpower against his enemies. Stewie loves singing his songs and rhymes as he dashes around his home. But as he grows up his beautiful blue tail starts to turn grey - he can't call himself Stewie the Blue anymore! He just doesn't feel quite so special anymore! And without his rhymes his home by the pond doesn't feel as special anymore. But when he meets his new friend the woodpecker, Stewie comes to understand that changing is all a part of growing up and that there are still many things that make him a very special skink!